1997
DOI: 10.1002/j.2161-007x.1997.tb00394.x
|View full text |Cite
|
Sign up to set email alerts
|

The Battered Committed Christian Woman: The Value Difference

Abstract: The authors review factors linked to the battered woman's return to the abusive environment and suggest an additional factorthe values of the woman. Moral development and some of the beliefs of the committed Christian woman are examined. The influence of these factors on her decision to remain in the abusive relationship are discussed. Interventions that accommodate to the framework of the committed Christian woman's value/belief system are explored. Counselors are also encouraged to explore their own value sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…They are told to stay with the Manetta et al 7 man, and are reminded of their vows to stay with their partner for better or for worse (Pagelow and Johnson, 1988;Smullens, 2001). Women often stay with abusive partners because of their religious beliefs and values (Griffin and Maples, 1997;Peake, 2001). These religious beliefs and values center around upholding the covenant of marriage.…”
Section: Church Attitudes Toward Domestic Violencementioning
confidence: 99%
See 2 more Smart Citations
“…They are told to stay with the Manetta et al 7 man, and are reminded of their vows to stay with their partner for better or for worse (Pagelow and Johnson, 1988;Smullens, 2001). Women often stay with abusive partners because of their religious beliefs and values (Griffin and Maples, 1997;Peake, 2001). These religious beliefs and values center around upholding the covenant of marriage.…”
Section: Church Attitudes Toward Domestic Violencementioning
confidence: 99%
“…Other reasons women stay with abusive partners are the ideas that women should be submissive to their husbands (Alsdurf and Alsdurf, 1988;Griffin and Maples, 1997;Stotland, 2000) and that women are perceived as men's possessions (Van Natta, 2001). Nason-Clark (1997) points out that some researchers have identified issues that clergy should be conscious of when counseling abuse victims and perpetrators.…”
Section: Church Attitudes Toward Domestic Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if divorced, a religious woman may fear for her placement in the afterlife (Ferraro & Johnson, 1983) or perceive remarriage as adulterous. If she wanted to end the relationship, tensions over how divorce affects her children, extended family, and her religious community create for her plausible (if not moral) grounds for returning home (Griffin & Maples, 1997).…”
Section: Conceptions Of Divorcementioning
confidence: 99%
“…These beliefs and practices include male domination over women, superior male morality, suffering as a female Christian virtue, and the importance of marital reconciliation (Heggen, 1996). Griffin and Maples (1997) suggested that FPC beliefs and values strongly influenced women in h s population who remained in abusive partnerships.…”
mentioning
confidence: 97%